Negócio jurídico processual na Justiça do Trabalho - Furlan, Gabriel Henrique Zani (2022)
The procedural legal business, despite not being a doctrinal fruit of this century, has an innovative normative provision arising from the Civil Procedure Code of 2015, which reinforced the autonomy of the parties and procedural cooperation without abandoning procedural publicism. Thus, it expressly provided for the possibility of the procedure being adjusted by the parties, according to the specificity of the demand, as well as making it possible to agree on its procedural burdens, powers, faculties and duties, before or during the process, provided that in processes involving rights that admit self-composition. Thus, the present work aimed to analyze the procedural legal business and the possibility of application in the work process from the perspective of protection and respect for fundamental labor rights, even if, for this, adaptations must be made. Thus, through a systematic interpretation and, using the hypothetical-deductive method, the present work abandons presumed or preconceived concepts that reject any discussion through a supposed maximum protection of the unavailability of labor rights, positioning itself against the normative issued in 2016 by the Superior Labor Court which, in view of the studies presented, is currently outdated in the face of law 13.467/2017 and the very provision of the digital judgment. In view of this, ideas developed by scholars are presented, as well as an evaluation provided in the procedural legislation itself, with emphasis on the requirements and judicial control, as is the case of judicial control of validity in the face of abusive insertion in an adhesion contract or in the case of manifests a situation of vulnerability on the part of one of the parties, while highlighting understandings and examples found in Brazilian Courts. Finally, the present work does not aim to end the discussion on the subject, but to provoke debate and bring the application of the procedural legal business in the labor field, without offending the protection of fundamental labor rights or the principles and peculiarities of the process. from work